PNRA: the South-Pole directory : user's manual - Biagioni, Stefania; Carlesi, Carlo; Romano, Giuseppe A.; Rossi, Lucio; Vannozzi, Daniele (1992)
In 1989, a working group was constitued at the "Istituto di Elaborazione della Informazione" of the Italian National Research Council (IEI-CNR), within the framework of the National Antarctic Research Programme (PNRA), with the scope of providing ENEA with consulting services and technical support in information processing. The primary objective was to design and implement an integrated information system which would be based on the Antarctic Data Bank. Antarctic Data concerns research in Earth Sciences, Oceanography, Physics of the Atmosphere, Cosmophysics, Biology and Environmental studies and Medical Sciences. The South-Pole Directory is the first multidisciplinary Antarctic directory which is accessible on-line on international network, via ASTRA system and via ESA-PID system. The implementation of the Directory has required more than 1 year with several readjustments to the original objective; at present, the Directory provides the user with a description of the research and the available data as well as the procedures to obtain data. Data can also be requested directly from the individual research-groups.